Attachment and Severity of Grief: The Mediating Role of Negative Appraisal and Inflexible Coping. (November 2013) - Delespaux, Emily; Ryckebosch-Dayez, Anne-Sophie; Heeren, Alexandre; Zech, Emmanuelle
According to the Dual Process Model of coping with bereavement (DPM; Stroebe & Schut, 1999), adjustment to bereavement involves a flexible oscillation between two types of coping strategies: loss-oriented (LO) and restoration-oriented (RO). This model postulates that extremely anxious or avoidant attachment disturbs the oscillation process by focusing more on one type of strategy, either LO or RO. The present study examined this assumption. We recruited 321 bereaved individuals who had lost a romantic partner. Our results showed that less negative appraisal of bereavement-related stressors, as well as higher use of RO strategies, mediated the link between attachment avoidance and low severity of grief reactions. However, the DPM variables were not found to mediate the link between attachment anxiety and elevated grief reactions. We discuss how these results provide an empirical basis of the DPM.